ChemInform Abstract: First Synthesis of Unexpected Functionalized Trifluoromethylated 8‐Oxa‐2, 4‐diazaspiro[5.5]undecanes via One‐Pot MCRs. Issue 6 (February 2015) - Li, Jia; Shi, Wei; Yang, WenXin; Kang, ZhangPing; Zhang, Min; Song, LiPing
Abstract The formed spiro compounds can be further dehydrated to (V) in the presence of thionyl chloride/pyridine.